Providing an Architecture Framework for Cyberjustice - Benoit A. Aubert; Gilbert Babin; Hamza Aqallal (Laws, 2014)
The paper illustrates how architecture can be used to show the contribution and the use of technology in the legal system. The models created enable the rapid identification of the stakeholders, their objectives, the technologies they use, and their goals. Such understanding helps decision makers ensure that the tools and processes enabled by information technology (IT) are aligned with the goals of the legal system. The preliminary framework developed in the paper shows the feasibility and the contribution of such models on a larger scale.